Avaliação física, química, microbiológica e pesquisa de Anticorpos anti-IgG em urina de cães (Canis familiaris) Linnaeus, 1785) naturalmente infectados por Leishmania (Leishmania) chagasi (Cunha & Chagas, 1937) - LIRA, Nadja Maria Silva de (2009)
In Canine Visceral Leishmaniasis (CVL) changes of urine patterns and the presence of anti-Leishmania sp. antibodies in it may reflect an immunomediated glomerular lesion. The goal of this study was to evaluate the physical, chemical and microbiological aspects of urine and also verify the presence of anti-Leishmania antibodies in the urine of dogs naturally infected by Leishmania (Leishmania) chagasi by using cystocentesis. Urine specimens were collected from 20 dogs, which all of them were serologically positive for Leishmania sp by ELISA test. Out of 20 samples, 70% showed different patterns of colors, follow by pH values changes (45%) and protein and blood contents (50%). Microorganisms were isolated in 35% of urine samples, with prevalence of Staphylococus spp. (20%), Shigella sonnei (15%), Streptococus spp. (5%) and Providencia stuartii (5%). On the other hand ELISA test was run in 22 samples by using serial dilutions (1:100, 1:50 and 1:25). The results showed that 4.54 % of the samples were positive at dilutions of 1:50 and 1:25. These data showed that protein and blood contents determination and the cystitis could be sugestive signs to evaluate in CVL, but also indicated the detection of antibodies in urine of CVL may be a good tool, but the sensibility and specificity must to be estimate in order to use this kind of test.